Formulation of Policy on the Implementation of Criminal Punishment Sanctions and Rehabilitation Against Children as Drug Abuse Perpetrators - Patmawanti, B. (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
The study concludes that the application of rehabilitation for children involved in narcotics abuse should prioritize child protection. Based on various court rulings, children who misuse narcotics and become involved in criminal activities should be seen as victims of their actions, not perpetrators who harm others. Therefore, rather than imprisonment, rehabilitation is the appropriate solution as it prevents harm and better protects the child’s future. Rehabilitation consists of medical rehabilitation to address addiction through treatment in designated facilities, and social rehabilitation to restore physical, mental, and social well-being in an integrated manner. This approach is considered the most humane and supportive for the child’s recovery. Furthermore, there is a need to evaluate and refine rehabilitation policies to break the cycle of narcotics abuse among children effectively. The goal is to create a policy framework that provides the most appropriate sanctions, promoting effective rehabilitation and preventing recidivism, focusing on legal and social reintegration.